2016
DOI: 10.1164/rccm.201507-1279oc
|View full text |Cite
|
Sign up to set email alerts
|

Short Stature and Access to Lung Transplantation in the United States. A Cohort Study

Abstract: Rationale: Anecdotally, short lung transplant candidates suffer from long waiting times and higher rates of death on the waiting list compared with taller candidates.Objectives: To examine the relationship between lung transplant candidate height and waiting list outcomes.Methods: We conducted a retrospective cohort study of 13,346 adults placed on the lung transplant waiting list in the United States between 2005 and 2011. Multivariable-adjusted competing risk survival models were used to examine associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
(24 reference statements)
0
24
0
Order By: Relevance
“…There may also be a selection bias for females who survive to transplant. Sell and colleagues demonstrated that patients (often females) with shorter stature have a 62% higher death or removal rate on the waitlist due to clinical deterioration . Those of short stature that make it to transplant may be better recipients.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be a selection bias for females who survive to transplant. Sell and colleagues demonstrated that patients (often females) with shorter stature have a 62% higher death or removal rate on the waitlist due to clinical deterioration . Those of short stature that make it to transplant may be better recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The three most common indications were ILD (including IPF), CF and COPD (excluding AATD). 7,8 Survival Results from our centre suggest superior survival compared with international registry data. Half of our transplant recipients are over 50 years of age, and 10% were between 60 and 65 years.…”
Section: Recipient Characteristicsmentioning
confidence: 78%
“…First, patients of short stature (<162 centimeters) have been shown to have a lower rate of transplantation and a higher rate of waitlist death when compared to waitlisted patients of average height in a national registry [20]. Second, patients with a sensitized antibody profile have a longer waitlist time and are less likely to receive a lung transplant [21].…”
Section: Disparities In Allocationmentioning
confidence: 99%